Diaspora nationalism and Jewish identity in Habsburg Galicia - Shanes, Joshua, 1971- (Cambridge University Press, 2012)
"This book explains the construction of the Jewish nation in Galicia, the process by which traditional Jews modernized, and the variety of identities they adopted"--